The Left in Latin America today. A conversation with Carlos Gaviria, Polo Democrático Alternativo de Colombia - León Vargas, Yamile (2016)
Interview with Carlos Gaviria, president of Polo Democrático Alternativo de Colombia by Yamile León, on the subject of The Left in Latin America.